Economics of Farm Forestry in Haryana - an Economically Viable and Ecologically Sustainable System - Sodhi, Harminder; Ansari, M. Y. (Indian Forester, 1996)
To improve the biological productivity as well as the economic return of the same piece of land, the different formats of farm forestry include peripheral planting on field boundaries, block plantation along with usual agricultural practices are being adopted in Haryana. The poplar planting has been selected for an indepth study in view of its important contribution towards rural economy. To study the economic results of the various plantations, the major component of Cost Benefit Analysis viz; Net Present Value (NPV), Benefit Cost Ratio (B : C ratio), Internal Rate of Return (IRR) and Average Annual Net Returns (AANR) are calculated for 4,5 and 6 years of rotations and poplar planting has been found to be more profitable than the traditional agricultural crops in Ambala, Kurukshetra and Yamunanagar Districts of Haryana.